O papel do prazer na caracterização da vida justa na "República" de Platão - João Gabriel da Silva Conque Santos (2022)
This thesis argues that the discussion on pleasure in Book IX of Plato’s Republic is far from being unimportant in the economy of this Platonic dialogue. In order to do so it will be necessary to show how such discussion is associated with what constitutes the kernel of the work, namely, the defense of justice as provider of true happiness. Indeed, Socrates is interested in showing that the just life is not only worth of living, but also the most pleasant. For our purposes, we present elements that show the extent to which a response to Glauco’s challenge requires, albeit in a secondary way, an approach involving the pleasures enjoyed by those who cultivate a life based on justice. In view of this, we analyze some passages of Republic with the aim of showing how nuanced the notion of pleasure in this work is. Finally, we examine the three demonstrations of superiority of the just life to the unjust life developed in Books VIII and IX, where we find crucial references to the theme of pleasure. By examining this triad of demonstrations, Socrates' reply to Glaucon's challenge will become clearer.